IDDF2019-ABS-0196 Long term outcomes of utilizing donation after circulatory death grafts in liver transplantation – an australian 12-year cohort study. (June 2019) - Sastry, Vinay; Pandya, Keval; Panlilio, Mara; West, Claire; Virtue, Susan; Wells, Mark; Crawford, Michael; Pulitano, Carlo; Strasser, Simone; McCaughan, Geoff; Majumdar, Avik; Liu, Ken
Abstract : Background: Organ shortage for liver transplantation (LT) is a major problem worldwide. Use of donation circulatory death donors (DCD) has been one strategy to expand the donor pool; however, data on long term outcomes in DCD graft recipients are mixed. We studied the characteristics, utilization and recipient outcomes of DCDs. Methods: We retrospectively studied adults who underwent deceased LT between 2006–2018. Donor and recipient data at LT and recipient outcomes were collected from a prospective database. Criteria for DCD selection at our center include all of the following: donor age <50years, BMI <30kg/m 2, and circulatory arrest within 30minutes of treatment withdrawal in otherwise suitable liver donors. The primary outcome of interest was graft survival (time to retransplantation or death). Results: During the study period (median follow-up 50.6months), 739 donors were utilized for LT with 53 (7.2%) being DCDs. Compared to donation after brain death donors (DBDs), DCDs were younger (30 vs. 50years), more likely to have history of predonation cardiac arrest (71.2% vs. 34.8%), had longer intubation time (3 vs. 2days), less inotrope requirements (32.7% vs. 7.8% on no agents) and higher AST (59 vs. 46U/L) (median values presented, all P <0.01). DCDs had shorter cold ischemia time (5.75 vs. 6.85hours, P =0.005) and higher donor risk index (Feng et al. 2006) (1.68 vs. 1.56, P <0.001). As per our unit policy, recipients of DCD grafts were less likely to be PSC (1.9 vs. 9.0%, P =0.076) or retransplant patients (0 vs. 6%, P =0.067). Similarly, DCD recipients did not receive split grafts (0 vs. 15.3%, P <0.001). The proportion of DCDs among utilized grafts increased from 4.8% (2006–2009) to 7.8% (2010–2012) and remained stable afterward. 157 patients experienced graft loss during follow-up (31 retransplants, 126 deaths). DCD grafts had similar long term graft survival compared to DBDs, although DCDs recipients with high preLT MELD (>20) appeared to have worse outcomes (figure 1 ). Conclusions: Long term outcomes of DCD grafts are similar to DBD grafts especially when matched with appropriately selected recipients (first transplant, nonPSC patients with low MELD).